2018
DOI: 10.1097/scs.0000000000004030
|View full text |Cite
|
Sign up to set email alerts
|

Metopism: a Study of the Persistent Metopic Suture

Abstract: Metopism, the persistence of the metopic suture in adulthood, is a clinically significant radiographic finding. In addition to masquerading as a fracture of the frontal bone, a persistent metopic suture may be associated with other clinically significant anatomical variations including frontal sinus abnormalities. Several geographically and craniofacially distinct populations have yet to be assessed for the prevalence of metopism. This study aimed to determine the prevalence of metopic sutures in adult crania … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 23 publications
0
22
0
2
Order By: Relevance
“…The MS may reside as a partial pattern or a complete pattern. The partial patterns expand upward from the nasion or downward from the bregma, different from the completes spanning from the bregma to the nasion [11,24,25]. The suture forms from the bregma and performs toward the nasion.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The MS may reside as a partial pattern or a complete pattern. The partial patterns expand upward from the nasion or downward from the bregma, different from the completes spanning from the bregma to the nasion [11,24,25]. The suture forms from the bregma and performs toward the nasion.…”
Section: Discussionmentioning
confidence: 94%
“…MS may be confused with midline fractures of the frontal bone in radiology in terms of clinical significance. In addition, studies have shown that MS is associated with other clinically significant findings, such as frontal sinus abnormality, cleft lip, visceral inversion, cleft palate, cretinism, and intelligence [11,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the frontal suture can remain open into adulthood in about 4% of women and 2% of men. 5 Estrogen has been shown to have an influence on cranial suture formation and closure, and females appear to close cranial sutures slower than males. 6 There are multiple cranial sutures (see images Figure 1(A) to (D)) and thus numerous possible distributions for cranial suture headache.…”
Section: Anatomymentioning
confidence: 99%